2021
DOI: 10.3895/rts.v17n46.12661
|View full text |Cite
|
Sign up to set email alerts
|

Nomofobia: uma análise bibliométrica

Abstract: Nomofobia, advindo da expressão “No-Mobile-Phone-Phobia”, designa-se ao transtorno ou fobia motivados por ficar sem o contato com o telefone celular. Objetiva-se mapear e quantificar a produção científica sobre o tema dependência tecnológica e nomofobia dentro do contexto mundial. A pesquisa foi realizada nos bancos de dados SciELO, LILACS e PubMed com os descritores (nomofobia) or (dependência tecnológica) or (nomophobia) or (technological dependence) or (technology dependence) or (dependencia tecnológica). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Studies on factors associated with smartphone addiction have focused on eastern countries and university populations (KHOURY et al, 2020;ALVES;ANTONIO;LAUX, 2021). Studies in this regard concerning Brazilian teenagers are scarce and have demonstrated that smartphone dependence is associated with younger teenager age, less sleep hours, more smartphone use during the weekends, complaints of neck pain and suspicions of Common Mental Disorder (CMD) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on factors associated with smartphone addiction have focused on eastern countries and university populations (KHOURY et al, 2020;ALVES;ANTONIO;LAUX, 2021). Studies in this regard concerning Brazilian teenagers are scarce and have demonstrated that smartphone dependence is associated with younger teenager age, less sleep hours, more smartphone use during the weekends, complaints of neck pain and suspicions of Common Mental Disorder (CMD) .…”
Section: Introductionmentioning
confidence: 99%